The Application of Multiple Intelligences in Islamic Religious Education - Ucup Supriatna; Zulvia Trinova; Samuel PD Anantadjaya; Mariana Puspa Dewi; irma M Nawangwulan (AL-ISHLAH: Jurnal Pendidikan, 2021)
This qualitative research aims to determine how crucial Multiple Intelligence is in Islamic religious learning. The method in this research is a theoretical study that tries to find hypotheses by examining various research sources and online media about Multiple Intelligence. The collecting data is by gathering some literature obtained from various articles, both accredited national journals and reputable international journals. Data analysis is done by mapping from the collected data and obtaining literature from multiple intelligences in Islamic Religious Education. The result of this research is that with the application of multiple intelligences, the teacher can map the condition of students based on their potential and interests and with the among system, the characteristics of students can be continuously fostered without being shackled to their "independence" to develop.